Preparation and application of high-density polyethylene / graphene oxide nano composite fiber membrane
The high-density polyethylene/graphene oxide nanocomposite fiber membranes were prepared through electrospinning technology, which solved the problems of low water recovery rate, membrane pollution and high energy consumption of the adsorption membrane of the existing water filtration device, and achieved efficient adsorption and removal of arsenic elements in water.
Patent Information
- Application Number
- CN202510193585.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The adsorption membrane of existing water filtration devices has problems such as low water recovery rate, membrane pollution and high energy consumption, and the adsorption performance of arsenic is insufficient, resulting in water contamination by arsenic.
Electrospinning technology is used to prepare high-density polyethylene/graphene oxide nanocomposite fiber membranes. By spinning graphene oxide powder and high-density polyethylene resin particles under an electrostatic field, a nanocomposite fiber membrane with high pore size distribution, huge specific surface area and uniform fiber diameter.
It improves the adsorption efficiency of arsenic in water, reduces membrane pollution and energy consumption, and enhances the attraction between water molecules and the membrane surface, forms a protective water layer and prevents pollutants from adhering.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional fiber materials, and specifically relates to a high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by electrospinning and its application in adsorbing and removing arsenic in water. Background Art
[0002] Electrospinning technology has simple equipment, convenient control, and low price. It is recognized as a simple, universal, and cost-effective method for mass production of nanomaterials. Its most advantageous aspect is that it can easily realize the compounding of multi-component materials through electrospinning. By adjusting and controlling the process parameters of electrospinning technology during the spinning process, a large number of nanofiber materials with various forms and microscopic pore structures can be produced. These nanofiber materials are widely used in battery energy, medical care, catalysis, and environmental engineering. The basic principle of electrospinning technology is that under high-voltage electrostatic conditions of 3-1000 kV, the positive electrode is connected to the polymer melt or solution at the needle tip, and the negative electrode is grounded. At this time, the dripping melt or liquid under pressure will produce surface tension, and when the electric field force can overcome the surface tension of the polymer droplets, a Taylor cone with an angle of about 40° will be generated on the droplet surface. Due to the continuous action of the electric field force, the charged polymer jet is stretched into fiber filaments with a diameter at the nanometer level, thereby realizing the spinning process under high-voltage electrostatic field. During the electrospinning process, the solvent evaporates under the action of the electrostatic field and the solute solidifies into fibers, and finally a fiber web or film with a diameter of nanometers is collected on the receiving device.
[0003] The number of people exposed to arsenic levels above 50 μg / L has exceeded 1.85 million nationwide, and the total number of people exposed to arsenic levels in drinking water exceeding 10 μg / L (national drinking water arsenic pollution standard) may exceed 19 million. Existing water filtration device adsorption membranes have certain problems such as low water recovery rate, membrane pollution and high energy consumption, and their adsorption of arsenic often does not meet expectations. If not replaced in time, the water will be contaminated by arsenic. Therefore, surface modification of adsorption membranes by electrospinning to improve the adsorption performance of adsorption membranes for arsenic has attracted widespread attention. Summary of the invention
[0004] In view of the problems of low water recovery rate and membrane pollution of existing arsenic adsorption membranes, the present invention proposes a high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by electrospinning, which has unique advantages such as good pore size distribution, small pore size level, outstanding fiber diameter uniformity and huge specific surface area, and can be used as an adsorption membrane for the adsorption and removal of arsenic in water.
[0005] To achieve the above object, the present invention adopts the following technical solutions: A high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by electrospinning, the preparation of which comprises the following steps: 1) adding graphene oxide powder to an organic solvent and dispersing the powder by ultrasonication to obtain a graphene oxide dispersion; 2) adding high-density polyethylene resin particles to the graphene oxide dispersion prepared in step 1), and stirring at a constant temperature of 80° C. until the particles are completely dissolved, to obtain a high-density polyethylene / graphene oxide mixed spinning solution; 3) Using the mixed spinning solution obtained in step 2) to perform electrospinning to obtain the high-density polyethylene / graphene oxide nanocomposite fiber membrane.
[0006] Furthermore, the edge oxidation degree of the graphene oxide powder in step 1) is 4%-10%.
[0007] Furthermore, the organic solvent in step 1) is decahydronaphthalene, liquid paraffin or p-xylene.
[0008] Furthermore, the mass concentration of the graphene oxide dispersion in step 1) is 15% to 25%.
[0009] Furthermore, in step 2), the mass concentration of high-density polyethylene in the mixed spinning solution is 15%-23%.
[0010] Furthermore, the process parameters of the electrospinning in step 3) are: the supply speed of the propulsion pump solution is 0.5-1.5 ml / h; the negative voltage is 1 KV, and the positive voltage is 10-20 KV; the speed of the drum collector motor is 500-1500 r / min; the spinning temperature is 20-35°C, and the time is 1-3h; the distance from the needle to the drum receiving device is 10-20 cm.
[0011] The high-density polyethylene / graphene oxide nanocomposite fiber membrane can be used for adsorption and removal of arsenic in water.
[0012] Specifically, the high-density polyethylene / graphene oxide nanocomposite fiber membrane is used as an adsorption membrane for adsorption and removal of arsenic in water.
[0013] Compared with the prior art, the present invention has the following advantages: 1) The high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by electrospinning in the present invention has higher hydrophilicity on the surface and in the pores, so that water molecules have a strong attraction with the membrane surface, forming a protective water layer, which can prevent pollutants from attaching and reduce membrane pollution.
[0014] 2) The high-density polyethylene / graphene oxide nanocomposite membrane prepared by electrospinning of the present invention has a higher pore size ratio and thus has a higher efficiency in adsorbing and intercepting pollutants such as arsenic. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 These are SEM images of high-density polyethylene fibers prepared from spinning solutions of different mass fractions in Examples 1 to 4, wherein a and b are 5000× and 10000× images with a mass fraction of 15%, c and d are 5000× and 10000× images with a mass fraction of 18%, e and f are 5000× and 10000× images with a mass fraction of 20%, and g and f are 5000× and 10000× images with a mass fraction of 23%.
[0016] Figure 2 These are SEM images of high-density polyethylene fibers prepared at different spinning voltages in Examples 5 to 7, where a and b are 5000× and 10000× images at a voltage of 10 kV, c and d are 5000× and 10000× images at a voltage of 13 kV, e and f are 5000× and 10000× images at a voltage of 16 kV, and g and f are 5000× and 10000× images at a voltage of 19 kV.
[0017] Figure 3 These are SEM images of high-density polyethylene fibers prepared at different spinning flow rates in Examples 8 to 10, where a and b are 5000× and 10000× images at a propulsion speed of 0.5 ml / h, c and d are 5000× and 10000× images at a propulsion speed of 0.8 ml / h, e and f are 5000× and 10000× images at a propulsion speed of 1.2 ml / h, and g and f are 5000× and 10000× images at a propulsion speed of 1.5 ml / h.
[0018] Figure 4 These are SEM images of high-density polyethylene / graphene oxide composite fibers prepared with different graphene oxide addition ratios in Examples 11 to 13, wherein a and b are 5000× and 10000× images of 0% GO, c and d are 5000× and 10000× images of 0.5% GO, e and f are 5000× and 10000× images of 1.0% GO, and g and f are 5000× and 10000× images of 2.0% GO. DETAILED DESCRIPTION
[0019] A high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by electrospinning, the preparation of which comprises the following steps: 1) adding graphene oxide powder to an organic solvent and dispersing the graphene oxide powder by ultrasonic to obtain a graphene oxide dispersion having a mass concentration of 15% to 25%; 2) adding high-density polyethylene resin particles to the graphene oxide dispersion prepared in step 1), stirring at a constant temperature of 80° C. until the particles are completely dissolved, to obtain a high-density polyethylene / graphene oxide mixed spinning solution, wherein the mass concentration of the high-density polyethylene is 15%-23%; 3) Using the mixed spinning solution obtained in step 2) to perform electrospinning to obtain the high-density polyethylene / graphene oxide nanocomposite fiber membrane.
[0020] Wherein, the organic solvent in step 1) is decahydronaphthalene, liquid paraffin or p-xylene.
[0021] Step 3) The process parameters of the electrospinning are: the supply speed of the propulsion pump solution is 0.5-1.5 ml / h; the negative voltage is 1 KV, and the positive voltage is 10-20 KV; the speed of the drum collector motor is 500-1500 r / min; the spinning temperature is 20-35°C, and the time is 1-3h; the distance from the needle to the drum receiving device is 10-20 cm.
[0022] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0023] The test steps for arsenate adsorption rate are as follows: a. Prepare a sodium arsenate solution with an initial concentration of 300±10 μg / L; b. using a vacuum filtration pump to pass the sodium arsenate solution through the high-density polyethylene / graphene oxide composite fiber membrane; c. Use a UV spectrophotometer to measure the concentration of sodium arsenate solution before and after filtration, and calculate the adsorption efficiency according to the following formula.
[0024] Arsenate adsorption rate calculation formula: , where (C p is the concentration of sodium arsenate solution after filtration, C f is the concentration of sodium arsenate solution before filtration) All parameters in the electrospinning process affect the morphology and performance of the final fiber. Therefore, only by determining relatively excellent process parameters can fibers with good microscopic morphology and excellent performance be prepared. The relevant parameters in the electrospinning process can be divided into three categories: solution properties, operation settings, and external environment. Among them, parameters related to the properties of the solution itself include solution mass fraction, solution viscosity, and surface tension; parameters related to operation settings include voltage, flow rate, drum speed, receiving distance, etc.; environmental factors such as temperature and humidity during the spinning process. These three categories have a crucial influence on the morphology of nanofibers prepared by static spinning. During the research process of this invention, multiple example experiments were carried out with different solution mass fractions, voltages, and flow rates.
[0025] Example 1 1) Preparation of electrospinning solution: The high-density polyethylene resin particles were placed in an electric constant temperature forced air drying oven and dried for 2 h. Then, 2.65 g of high-density polyethylene resin particles were weighed and added in batches to a 200 ml flask containing 15 g of p-xylene (continue adding after part of the high-density polyethylene resin is completely dissolved). The mixture was stirred evenly on a constant temperature magnetic stirrer at 80 °C and 600 rpm for about 8 h to ensure that all the high-density polyethylene resin particles were fully dispersed in p-xylene, thereby obtaining a high-density polyethylene polymer solution with a mass fraction of 15%.
[0026] 2) Preparation of high-density polyethylene fiber by electrospinning: The prepared high-density polyethylene solution was loaded into a 10ml disposable syringe with a 0.88mm steel needle and fixed in the propulsion pump. A layer of tin foil was wrapped on the drum collector to receive the prepared high-density polyethylene fiber. The positive electrode of the power supply was connected to the steel syringe needle, and the negative electrode of the power supply was connected to the drum receiving device. Turn on the motor of the drum receiving device. After the drum device speed reaches 800rpm and rotates smoothly, turn on the syringe propulsion pump, set the propulsion speed to 0.8 ml / h, adjust the negative pressure of the high-voltage power supply to 1KV, the positive pressure to 13kV, the distance from the needle to the drum receiving device to 15 cm, the spinning temperature to 25℃, the spinning time to 3 h, and perform electrospinning. The high-density polyethylene droplets are stretched into fibers under the action of the high-voltage electrostatic field, and the solvent is fully evaporated by vacuum drying at 50℃ for 2h to obtain high-density polyethylene fibers.
[0027] Example 2 Step 1) Prepare a high-density polyethylene polymer solution with a mass fraction of 18%, and the remaining operations are the same as in Example 1.
[0028] Example 3 Step 1) Prepare a high-density polyethylene polymer solution with a mass fraction of 20%, and the remaining operations are the same as in Example 1.
[0029] Example 4 Step 1) Prepare a high-density polyethylene polymer solution with a mass fraction of 23%, and the remaining operations are the same as in Example 1.
[0030] The SEM images of the high density polyethylene fibers prepared in Examples 1 to 4 are as follows: Figure 1 The diameter results are shown in Table 1.
[0031] Table 1 Comparison of diameters of high-density polyethylene fibers prepared from spinning solutions with different mass fractions
[0032] Depend on Figure 1As can be seen from the results in Table 1, entanglement occurs on the high-density polyethylene fiber prepared in Example 1, and there are spherical beads and flocculent structures. The reason for this phenomenon is that the low mass fraction of the spinning solution leads to a small surface tension of the solution, and the polymer droplets cannot be fully stretched into filaments at the needle tip and form a good Taylor cone. The droplets that are not fully stretched by the electric field force fall on the fiber to form a beaded structure (a, b). The beaded structure on the high-density polyethylene fiber prepared in Example 2 is reduced, the degree of entanglement between fibers is reduced, the nanofibers are of different thicknesses, and the uniformity needs to be improved (c, d). The high-density polyethylene fiber prepared in Example 3 has a good morphology, no entanglement and spherical beaded structure, indicating that nanofibers with uniform diameter can be obtained by static spinning at this mass fraction. The average diameter of the high-density polyethylene fiber prepared in Example 4 is much higher than that of the sample in Example 3. It can be seen that selecting an appropriate spinning solution concentration not only helps the fiber to fully extend and reduce defects such as beads, but also effectively improves the average diameter and fiber uniformity of electrospun nanofibers, among which the effect of a mass fraction of 20% is better.
[0033] Embodiment 5: 1) Preparation of electrospinning solution: Place the high-density polyethylene resin particles in an electric constant temperature forced air drying oven and dry them for 2 h. Then weigh 3.75 g of high-density polyethylene resin particles and add them in batches into a 200 ml flask containing 15 g of p-xylene (continue adding after part of the high-density polyethylene resin is completely dissolved). Stir evenly on a constant temperature magnetic stirrer at 80 °C and 600 rpm for about 8 h to ensure that all the high-density polyethylene resin particles are fully dispersed in p-xylene, thereby obtaining a high-density polyethylene polymer solution with a mass fraction of 20%.
[0034] 2) Preparation of high-density polyethylene fiber by electrospinning: The prepared high-density polyethylene solution was loaded into a 10ml disposable syringe with a 0.88mm steel needle and fixed in the propulsion pump. A layer of tin foil was wrapped on the drum collector to receive the prepared high-density polyethylene fiber. The positive electrode of the power supply was connected to the steel syringe needle, and the negative electrode of the power supply was connected to the drum receiving device. Turn on the motor of the drum receiving device. After the speed of the drum device reaches 800rpm and rotates smoothly, turn on the syringe propulsion pump, set the propulsion speed to 0.8 ml / h, adjust the negative pressure of the high-voltage power supply to 1KV, the positive pressure to 10kV, the distance from the needle to the drum receiving device to 15 cm, the spinning temperature to 25℃, the spinning time to 3 h, and perform electrospinning. The high-density polyethylene droplets are stretched into fibers under the action of the high-voltage electrostatic field, and the solvent is fully evaporated by vacuum drying at 50℃ for 2h to obtain high-density polyethylene fibers.
[0035] Example 6 In step 2), the positive voltage of the high voltage power supply is adjusted to 16 kV, and the remaining operations are the same as those in Example 5.
[0036] The prepared nanocomposite fiber membrane was subjected to an arsenate adsorption rate test. The results showed that the permeation concentration of the sodium arsenate solution after filtration through the composite membrane was 219.87 μg / L, and the adsorption rate was 26.71%.
[0037] Example 7 In step 2), the positive voltage of the high voltage power supply is adjusted to 19 kV, and the remaining operations are the same as those in Example 5.
[0038] The SEM images of the high density polyethylene fibers prepared in Examples 5-7 are as follows: Figure 2 The diameter results are shown in Table 2.
[0039] Table 2 Comparison of diameters of high-density polyethylene fibers prepared at different spinning voltages
[0040] Depend on Figure 2 As shown in the results of Table 2, the high-density polyethylene fibers prepared in Example 5 have spherical bead defects, and the thickness uniformity of the fiber diameter is low. The surface of the high-density polyethylene fibers prepared in Example 6 is relatively smooth, and the diameter is uniform. The overall fiber morphology is good, without defects such as beading, filaments, and entanglement. This shows that the high-voltage electrostatic field force completely overcomes the surface tension of the polymer droplets at this time, and the strong electric field force gives the jet a greater tensile force and a higher acceleration. It can be fully extended in the electric field, and finally prepares high-density polyethylene fibers with a lower diameter. The high-density polyethylene fibers prepared in Example 7 have flocculent defects and filaments. It can be seen that the magnitude of the voltage determines the intensity of the electrostatic field during the spinning process, and the relationship between the electric field intensity and the surface tension of the solution leads to changes in the fiber morphology. When the electrostatic field strength is not enough to overcome the surface tension of the solution, the tensile stress of the electrostatic field is small, the droplets at the needle tip gather, and the polymer jet cannot be fully extended into fiber filaments in the electrostatic field, forming flocculent and beading defects, and the fiber diameter and uniformity also need to be improved; when the electrostatic field strength far exceeds the surface tension of the droplets, the solvent evaporates quickly, the Taylor cone is not stable enough, and the excessively fast jet acceleration leads to a reduction in the time it spends in the electrostatic field, thereby forming a flocculent structure and parallel filaments on the fiber. Therefore, a voltage of 16kV is better.
[0041] Example 8 1) Preparation of electrospinning solution: Place the high-density polyethylene resin particles in an electric constant temperature forced air drying oven and dry them for 2 h. Then weigh 3.75 g of high-density polyethylene resin particles and add them in batches into a 200 ml flask containing 15 g of p-xylene (continue adding after part of the high-density polyethylene resin is completely dissolved). Stir evenly on a constant temperature magnetic stirrer at 80 °C and 600 rpm for about 8 h to ensure that all the high-density polyethylene resin particles are fully dispersed in p-xylene, thereby obtaining a high-density polyethylene polymer solution with a mass fraction of 20%.
[0042] 2) Preparation of high-density polyethylene fiber by electrospinning: The prepared high-density polyethylene solution was loaded into a 10ml disposable syringe with a 0.88mm steel needle and fixed in the propulsion pump. A layer of tin foil was wrapped on the drum collector to receive the prepared high-density polyethylene fiber. The positive electrode of the power supply was connected to the steel syringe needle, and the negative electrode of the power supply was connected to the drum receiving device. Turn on the motor of the drum receiving device. After the speed of the drum device reaches 800rpm and rotates smoothly, turn on the syringe propulsion pump, set the propulsion speed to 0.5 ml / h, adjust the negative pressure of the high-voltage power supply to 1KV, the positive pressure to 16kV, the distance from the needle to the drum receiving device to 15 cm, the spinning temperature to 25℃, the spinning time to 3 h, and perform electrospinning. The high-density polyethylene droplets are stretched into fibers under the action of the high-voltage electrostatic field, and the solvent is fully evaporated by vacuum drying at 50℃ for 2h to obtain high-density polyethylene fibers.
[0043] Example 9 In step 2), the propulsion speed is set to 1.2 ml / h, and the remaining operations are the same as in Example 8.
[0044] Example 10 In step 2), the propulsion speed is set to 1.5 ml / h, and the remaining operations are the same as those in Example 8.
[0045] The SEM images of the high-density polyethylene fibers prepared in Examples 8-10 are as follows: Figure 3 The diameter results are shown in Table 3.
[0046] Table 3 Comparison of diameters of high-density polyethylene fibers prepared at different spinning flow rates
[0047] Depend on Figure 3As shown in the results of Table 3, the uniformity of the high-density polyethylene fiber prepared in Example 8 is slightly insufficient, and there is a phenomenon of paralleling. The diameter of the high-density polyethylene fiber prepared in Example 9 is significantly increased, and the uniformity is further reduced. The high-density polyethylene fiber prepared in Example 10 has a flocculent structure, the fiber diameter is significantly increased, and the uniformity is further reduced. It can be seen that the flow rate of the spinning solution is not only directly related to the stability of the jet in the spinning process and the average diameter of the nanofiber, but also determines the work efficiency of large-scale production of fibers. Beyond a certain limit, the fiber diameter rises sharply. The reason for the increase in diameter is that the increase in spinning flow causes the jet to become larger. Because the electric field force and the distance from the jet to the receiving roller are fixed, the solvent volatilization amount remains unchanged and the solute increases, which is manifested in the fiber as an increase in fiber diameter. The main reason for the decrease in uniformity and the appearance of flocculent structure is that the increase in flow rate is manifested as an increase in droplet diameter at the needle head. Under the condition of the same electric field force, the jet cannot be evenly split.
[0048] Taking into account the effects of various spinning process parameters on the microstructure of the fiber, the parameters finally selected at room temperature were 20% mass fraction of spinning solution, 16 kV spinning voltage, 0.8 ml / h flow rate, 800 rpm drum speed, and 15 cm receiving spacing. The same process parameters were also used in the subsequent preparation of high-density polyethylene / graphene oxide nanocomposite fiber membranes.
[0049] Embodiment 11: 1) Preparation of high-density polyethylene / graphene oxide electrospinning solution: Weigh graphene oxide powder with an edge oxidation degree of 4-10%, disperse it in p-xylene, and ultrasonically disperse it at 300w for 20min to make sure that there are no obvious particles at the bottom of the dispersed liquid. Then, high-density polyethylene particles are added to the ultrasonically dispersed graphene oxide dispersion to finally obtain an electrospinning solution with a graphene oxide mass fraction of 0.5% and a high-density polyethylene mass fraction of 20%.
[0050] 2) Preparation of high-density polyethylene / graphene oxide nanocomposite fibers by electrospinning: The prepared electrospinning solution was loaded into a 10ml disposable syringe with a 0.88mm steel needle and fixed in the propulsion pump. A layer of tin foil was wrapped on the drum collector to receive the prepared high-density polyethylene fibers. The positive electrode of the power supply was connected to the steel syringe needle, and the negative electrode of the power supply was connected to the drum receiving device. The motor of the drum receiving device was turned on. After the speed of the drum device reached 800rpm and the rotation was stable, the syringe propulsion pump was turned on, the propulsion speed was set to 0.8ml / h, the negative pressure of the high-voltage power supply was adjusted to 1KV, the positive pressure to 16kV, the distance from the needle to the drum receiving device was 15 cm, the spinning temperature was 25℃, the spinning time was 3 h, and electrospinning was performed. The high-density polyethylene droplets in the electrospinning solution were stretched into fibers under the action of the high-voltage electrostatic field, and the solvent was fully evaporated by vacuum drying at 50℃ for 2h to obtain high-density polyethylene / graphene oxide nanocomposite fibers.
[0051] The prepared nanocomposite fiber membrane was subjected to an arsenate adsorption rate test. The results showed that the permeation concentration of the sodium arsenate solution after filtration through the composite membrane was 97.74 μg / L, and the adsorption rate was 67.42%.
[0052] Example 12 In the electrospinning solution prepared in step 1), the mass fraction of graphene oxide is 1.0%, and the mass fraction of high-density polyethylene is 20%. The remaining operations are the same as those in Example 11.
[0053] The prepared nanocomposite fiber membrane was subjected to an arsenate adsorption rate test. The results showed that the permeation concentration of the sodium arsenate solution after filtration through the composite membrane was 60.51 μg / L, and the adsorption rate was 79.83%.
[0054] Embodiment 13 In the electrospinning solution prepared in step 1), the mass fraction of graphene oxide is 2.0%, and the mass fraction of high-density polyethylene is 20%. The remaining operations are the same as those in Example 11.
[0055] The prepared nanocomposite fiber membrane was subjected to an arsenate adsorption rate test. The results showed that the permeation concentration of the sodium arsenate solution after filtration through the composite membrane was 67.05 μg / L, and the adsorption rate was 77.65%.
[0056] The SEM images of high-density polyethylene / graphene oxide nanocomposite fibers prepared in Examples 11-13 are as follows: Figure 4 The diameter results are shown in Table 4.
[0057] Table 4 Comparison of diameters of high-density polyethylene / graphene oxide nanocomposite fibers prepared with different graphene oxide mass fractions
[0058] Depend on Figure 4 As can be seen from the results in Table 4, when graphene oxide is not added, the adsorption of arsenate by the fiber membrane is driven by pressure only, and only the sieving effect works, that is, it is a simple physical adsorption, and its adsorption rate is only 26.71%. The adsorption rate of arsenic by the high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by adding graphene oxide is significantly improved, and it increases with the increase of graphene oxide addition before reaching the adsorption rate limit. When the mass fraction of graphene oxide used is 1%, the adsorption rate reaches the maximum value of 79.83%, and the fiber morphology is good at this time, without obvious defects, and the diameter and pore size are uniform. This is because the GO doped in the composite fiber membrane has oxygen-containing hydrophilic functional groups such as hydroxyl and carboxyl, which can generate negative charges on the surface of the fiber membrane, and the negative charge of the arsenate ion and the negative charge of the functional group aggravate the Donnan effect. At this time, the filtration mechanism of the fiber membrane has not only the sieving effect of physical adsorption but also the Donnan effect of chemical adsorption, which is ultimately manifested as an increase in the adsorption rate of arsenate ions.
[0059] In summary, the present invention prepares a high-density polyethylene / graphene oxide nanocomposite fiber membrane by an electrospinning method, which can achieve effective adsorption of arsenic in water.
[0060] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a high-density polyethylene / graphene oxide nanocomposite fiber membrane, characterized in that: The following steps are involved: 1) adding graphene oxide powder to an organic solvent and dispersing the powder by ultrasonication to obtain a graphene oxide dispersion; 2) adding high-density polyethylene resin particles to the graphene oxide dispersion prepared in step 1), and stirring at a constant temperature of 80° C. until the particles are completely dissolved, to obtain a high-density polyethylene / graphene oxide mixed spinning solution; 3) Using the mixed spinning solution obtained in step 2) to perform electrospinning to obtain the high-density polyethylene / graphene oxide nanocomposite fiber membrane.
2. The method for preparing a high-density polyethylene / graphene oxide nanocomposite fiber membrane according to claim 1, characterized in that: The organic solvent in step 1) is decahydronaphthalene, liquid paraffin or p-xylene.
3. The method for preparing a high-density polyethylene / graphene oxide nanocomposite fiber membrane according to claim 1, characterized in that: The mass concentration of the graphene oxide dispersion in step 1) is 15% to 25%.
4. The method for preparing a high-density polyethylene / graphene oxide nanocomposite fiber membrane according to claim 1, characterized in that: Step 2) The mass concentration of high-density polyethylene in the mixed spinning solution is 15%-23%.
5. The method for preparing a high-density polyethylene / graphene oxide nanocomposite fiber membrane according to claim 1, characterized in that: Step 3) The process parameters of the electrospinning are: the supply speed of the propulsion pump solution is 0.5-1.5 ml / h; the negative voltage is 1 KV, and the positive voltage is 10-20 KV; the speed of the drum collector motor is 500-1500 r / min; the spinning temperature is 20-35°C, and the time is 1-3h; the distance from the needle to the drum receiving device is 10-20 cm.
6. A high-density polyethylene / graphene oxide nanocomposite fiber membrane prepared by the method as claimed in claim 1.
7. Use of the high-density polyethylene / graphene oxide nanocomposite fiber membrane as claimed in claim 6 in adsorbing arsenic in water.
8. The use according to claim 7, characterized in that: Specifically, the high-density polyethylene / graphene oxide nanocomposite fiber membrane is used as an adsorption membrane to adsorb and remove arsenic in water.
Citation Information
Patent Citations
Graphene-oxide-modified phenolic-resin-based ultrafine porous carbon fiber and preparation method thereof
CN103215693A
High-strength polyethylene / graphene nano composite film and preparation method thereof
CN115260638A
Carbon nanotube based membrane and methods of manufacturing
WO2021225958A1
Compositions and methods for separating metals and / or minerals from a source material using froth flotation
WO2023193018A1